Foody box sebagai tempat penyimpanan food model yang praktis dan efisien - Dina Fadhilah; Ayu Triani; Almira Sitasari (Health Educational Laboratory, 2024)
Errors in estimating the size of the portion of food consumed will affect the quality of the estimate and result in inaccurate amounts of nutrients consumed by a person. One of the teaching aids in delivering nutrition education material is food ingredients or artificial food (food models). Visualization of balanced nutrition messages that display food models displaying food and drink offerings at each meal time needs to be socialized so that it becomes a guide for people's eating. The aim of this research is to create a food storage box model that is practical and efficient for use with a model of food contents arranged like a tumpeng/food pyramid. This research method is quantitative research with a research and development (R&D) design. This method was chosen to produce a particular product and test the effectiveness of the product starting with: 1). Background data collection, 2). Product manufacturing planning, 3). Make a product draft, 4). Initial trials, 5). Revision of product trials, 6) Product implementation tests, 7). Improvement final product refinement 8). Product socialization and implementation. Quantitative data on product feasibility is shown in the presentation of feasibility test results. Research Results: To determine the feasibility of using this box, the researcher asked the subject 5 questions: 1). 87.5% of subjects considered the shape/design of the box to be appropriate, 2). How to open the box 95.8% of subjects rated it as feasible, 3). How to close the box 95.8% of subjects rated it as feasible, 4). How to use the food in a box model. 95.8% of subjects rated it as feasible and 5). The usefulness of the box was rated as 100% feasible by the subjects. The conclusion of the research is that from the 5 questions asked by the researchers, the presentation of the suitability assessment of the box is >80%, so it can be concluded that this box is suitable for use as a media for learning and promoting nutrition.